COVID-19-related hospital admission in spouses of partners in at-risk occupations - Jens Peter Ellekilde Bonde; Luise Mølenberg Begtrup; David Coggon; Johan Høy Jensen; Esben Meulengracht Flachs; Kristina Jakobsson; Christel Nielsen; Kerstin Nilsson; Lars Rylander; Andreas Vilhelmsson; Kajsa Ugelvig Petersen; Sandra Søgaard Tøttenborg (Nordic Association of Occupational Safety and Health (NOROSH), 2023)
OBJECTIVE: This study aimed to quantify the risk of COVID-19-related hospital admission in spouses living with partners in at-risk occupations in Denmark during 2020-21.METHODS: Within a registry-based cohort of all Danish employees (N=2 451 542), we identified cohabiting couples, in which at least one member (spouse) held a job that according to a job exposure matrix entailed low risk of occupational exposure to SARS-CoV-2 (N=192 807 employees, 316 COVID-19 hospital admissions). Risk of COVID-19-related hospital admission in such spouses was assessed according to whether their partners were in jobs with low, intermediate or high risk for infection. Overall and sex-specific incidence rate ratios (IRR) of COVID-19-related hospital admission were computed by Poisson regression with adjustment for relevant covariates.RESULTS: The risk of COVID-19-related hospital admission was increased among spouses with partners in high-risk occupations [adjusted IRR (IRRadjadjadjCONCLUSIONS: SARS-CoV-2 transmission at the workplace may pose an increased risk of severe COVID-19 among spouses in low-risk jobs living with partners in high-risk jobs, which emphasizes the need for preventive measures at the workplace in future outbreaks of epidemic contagious disease. When available, effective vaccines seem essential.